EFFORTS TO MAINTAIN THE ECONOMIC SUSTAINABILITY OF FARMER HOUSEHOLDS IN THE VILLAGE - Sulhan Manaf; Nurjanna Ladjin; Ahmadun (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
In poor economic conditions and to survive, either in the form of strategies or solutions internally (strategies carried out individually among family members) or externally (strategies carried out outside the scope of family members and interacting directly with the community). They do this in order to survive. Strategy is a way of life in dealing with an affair or problem, so that the matter or problem can be carried out well and correctly. Better livelihoods can reduce poverty levels and improve the welfare of households in a society. This can be overcome with community strategies to be able to have a sustainable livelihood. Household strategy of life refers to the patterns formed by various efforts that humans use to fulfill the life requirements they need and to solve the problems they face. In this research, several survival strategies for farming households in the village that were implemented were saving on family expenses, seeking additional income, and establishing a life of mutual cooperation with neighbors and relatives.